2019
DOI: 10.24200/sci.2019.52384.2683
|View full text |Cite
|
Sign up to set email alerts
|

Thermophoresis and Brownian motion effects of nanoparticles on Radiative heat transfer in Hiemenz flow: Using Spectral Method

Abstract: This study presents a theoretical investigation into thermophoresis andBrownian motion e ects on radiative heat transfer in the neighborhood of stagnation point. Thermophoresis and Brownian motion play an important role in thermal and mass concentration analyses, which help to comprehend the major ideas in the disciplines of science and technology. An electrically conducting nano uid was described by the Buongiorno transport model. The power-law form of the stretching wall velocity made the similarity solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Shafiq et al 11 examined the thermal transportation of Walters' B nanofluid over an extending surface. Iqbal et al 12 examined the Brownian motion of nanoparticles in the host fluid and found that Brownian motion enhances the base fluid temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Shafiq et al 11 examined the thermal transportation of Walters' B nanofluid over an extending surface. Iqbal et al 12 examined the Brownian motion of nanoparticles in the host fluid and found that Brownian motion enhances the base fluid temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies in which spectral-based linearization methods have been applied to understand the dynamics of heat and mass transfer problems include, but are not limited to. [24][25][26][27][28] In each of these studies, the technique was reported to be accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Idowu and Falodun 15 explored heat and mass transport of an MHD non‐Newtonian nanoliquid with Soret–Dufour as well as thermophoresis effect. Iqbal et al 16 studied nanoparticles in radiative heat transport in Hiemenz motion under the influence of thermophoresis as well as Brownian motion. A recent study by Rout et al 17 examined heat transport correlation for a cross‐flow jet impingement.…”
Section: Introductionmentioning
confidence: 99%